Wine industry competitiveness: A survey of the Shawnee Hills American Viticultural Area - C. M. Rendleman; Garrett A. Hoemmen; Ira Altman; Brad Taylor; Wanki Moon; Sylvia Smith (Wine Economics and Policy, 2016)
There is a growing consumer preference for regional or "terroir" based products (Guy 2011). The designation of American Viticultural Area (AVA) status has the potential to increase the development of consumer identification with regional wine products. The presence of a distinguishing terroir is one of the prerequisites for the establishment of a federally recognized AVA. The Tobacco Tax and Trade Bureau (TTB) granted the Shawnee Hills, located in southern Illinois, this designation at their request in 2006 (MKF 2005). The goal of the present research is to determine the key factors enhancing or constraining the competitive performance of wine businesses in the Shawnee Hills AVA. A winery competitiveness survey was administered to all owner/operators in the Shawnee Hills to determine whether the infrastructure was in place to sustain a regional wine quality program. The specific aim of this survey was to understand key factors influencing the competitive performance of wine businesses in the Shawnee Hills AVA. Shawnee Hill's AVA winery owner/operators regard increases in regional tourism, growth in the US wine market continuous innovation, unique services and processes, and flow of information from customers to have the most enhancing effects on their businesses, and that confidence/trust in Illinois state political systems, tax systems, and administrative/bureaucratic regulations were the most constraining factors. Furthermore the Shawnee Hills AVA has growing competition, yet consists of innovative winery owners. It may currently lack external financial support, but with a community focus on product differentiation, the Shawnee Hills AVA has a chance, owners believe, to capture a portion of the growing market for regional products.
Keywords: 330; Wine Industry Competitiveness